Pengaruh Manajemen Sumber Daya Manusia terhadap Kinerja Ekonomi Organisasi di SMK YPUI Parung - Rahmat Setiabudi; Jamaludin Jamaludin; Abdul Husenudin (Al-Kharaj: Jurnal Ekonomi, Keuangan & Bisnis Syariah, 2026)
Human resource management is a strategic factor in supporting the performance of educational organizations, particularly in dealing with limited resources and increasing demands for service quality. In vocational schools, organizational economic performance is not interpreted as financial profit, but as the ability of institutions to manage resources efficiently, effectively, and productively. This study aims to analyze the effect of human resource management on organizational economic performance at SMK YPUI Parung. This research employs a quantitative approach using a survey method. Primary data were collected through questionnaires distributed to teachers and educational staff, while secondary data were obtained from school administrative documents. The object of this study includes human resource management and organizational economic performance, with SMK YPUI Parung as the research locus. Data were analyzed using simple linear regression with the assistance of statistical software. The preliminary assumption of this study is that human resource management has a positive and significant effect on the organizational economic performance of the school.